Mid-term Outcomes of Renal Branches Versus Renal Fenestrations for Thoraco-abdominal Aneurysm Repair. Issue 2 (August 2016) - Martin-Gonzalez, T.; Mastracci, T.; Carrell, T.; Constantinou, J.; Dias, N.; Katsargyris, A.; Modarai, B.; Resch, T.; Verhoeven, E.; Haulon, S.
Abstract : Objective/Background: The objective was to investigate renal outcomes following endovascular repair of thoraco-abdominal aortic aneurysms (TAAA) comparing fenestrations with branches for the renal arteries. Methods: Renal outcomes following TAAA endovascular repair performed with renal branches were collected from five high volume European centers and compared with renal outcomes following TAAA endovascular repair performed with renal fenestrations at one center. Renal re-intervention and occlusion rates, and freedom from any renal outcome and death were analyzed by patient and target vessel. Estimated glomerular filtration rate (eGFR) was calculated and collected pre-operatively and at the last available follow up. Results: In total, 449 patients were included in this retrospective study (235 treated with branched devices [BEVAR] and 214 with fenestrated devices [FEVAR]). Altogether, 856 renal vessels were analyzed (445 perfused by branches and 411 by fenestrations). Both groups were comparable except for sex and smoking habits. Technical success rates were 95% and 99%, respectively. Mean ± SD follow up was 19 ± 18 months after BEVAR and 24 ± 20 months after FEVAR. During follow up, renal re-intervention rates were similar in both groups (4.7% vs. 5.2%). The renal occlusion rate was significantly higher following BEVAR (9.6% vs. 2.3%; p  < .01), and the 2 year freedom for renal occlusion rate was 90.4% (SE 85.8–95.3%) following BEVAR and 97.1% (SE 94.6–99.7%) following FEVAR ( p  < .01). During follow up, a 12% median decrease in eGFR was observed following BEVAR versus 9% following FEVAR (non-significant). The 2 year survival rates were 73.4% (SE 66.6–80.9%) and 81.8% (SE 76.1–87.9%) following BEVAR and FEVAR, respectively. Conclusion: Mid-term renal outcomes following endovascular repair of TAAA are satisfactory. Endograft designs incorporating renal fenestrations rather than renal branches are associated with significantly lower occlusion rates. A prospective trial is now required to confirm these results.